Cu(II)-based coordination polymers: structural determination and protective effect on myocardial ischemia-reperfusion injury by reducing inflammatory response. Issue 1 (2nd January 2021) - Liu, Ming-Jie; Na, Ri-Song; Bi, Fu-Long; Tang, Wen-Li; Yang, Hong-Xia
Abstract: In this work, two Cu(II)-containing coordination polymers, namely, [Cu2 (L)2 (dpyb)(H2 O)4 ]·6H2 On (1 ) and [Cu2 (L)2 (dpyb)](CH3 CN)2 n (2 ) have been hydrothermally synthesized based on a substituted thiophene carboxylic acid 3, 3′-(thiophene-2, 5-diyl)dibenzoic acid (H2 L) and auxiliary N-donor co-ligand 1, 4-di(pyridin-4-yl)benzene (dpyb). Furthermore, the protective effect of compounds 1 and 2 on myocardial ischemia-reperfusion injury (MIRI) was evaluated and the specific was explored. The real-time reverse transcription-polymerase chain reaction (RT-PCR) revealed the down-regulated relative expression of the nf-κb and mapk genes after compound treatment. The enzyme-linked immunosorbent assay (ELISA) suggested the inhibitory of the compound on inflammatory cytokines IL1-β and TNF-α releasing.